Learning Motivation of Science Education Students on Biochemical Learning Outcomes: Profile and Correlation - Dea Santika Rahayu; Setia Rahmawan; Ayu Lestari; Ismun Nisa Nadhifah; Paskalia Pradanti (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
Learning motivation is an important aspect that can encourage students to carry out learning. Self-Determination Theory assumes that individuals have basic psychological needs to develop and learn which include competence, relatedness, and autonomy. This study aims to characterize student learning experiences in the affective aspect (motivation) related to learning outcomes (Theory and Practicum). The researchers used the descriptive correlation research design to describe students' motivation profiles and provide an overview of the relationship between chemistry learning motivation and learning outcomes in Biochemistry courses (Theory and Practicum). The data was collected using the AMS-Chemistry instrument, which was analyzed through descriptive statistics and Pearson correlation analysis. The AMS-Chemistry consists of a motivation subscale, extrinsic motivation, and intrinsic motivation, which are spread into 28 statements, which was validated and reliable. The research subjects used 40 students from a total population of 118 people. Overall, the motivation profile to learn chemistry in science education students on the amotivation subscale tends to disagree, extrinsic motivation with a tendency to agree, and the subscale of intrinsic motivation with a tendency to strongly agree. Student learning outcomes in Biochemistry (Theory) courses have a significant relationship with extrinsic motivation (external regulation, introjected regulation, identified regulation) and intrinsic motivation (to know, to experience), while in Biochemistry (Practicum) has a significant relationship with motivation extrinsic (identified regulation) and intrinsic motivation (to know, to accomplish, to experience). This finding is a reflection that can be used as a reference in developing further learning.